PATTERN OF MINERALISATION - A REVIEW - Ragav N V, Hemanth; Santhanam, Archana (International Journal of Psychosocial Rehabilitation, 2020)
The tooth develops through different chronological stages. Collagen is the protein in connective tissue as well as in hard tissue, bone, dentin, cementum, and even the mineralizing ligament of the epiphyseal growth plate. Hard tissue is mineralized and has a firm intercellular framework. Tooth development and mineralization are processes that derive from different tissue interactions, such as ectodermal and mesenchymal. These interactions are responsible for the formation of unique structures with a specific chemical composition. Despite differences, mineralized tissues are similar, deriving from highly concentrated extracellular processes involving matrix proteins, proteases, and mineral ion fluxes that regulate mineral crystal nucleation, growth, and organization. There are two theories-—they are collagen template-mediated mineralization and matrix vesicle-mediated mineralization. Mineralized tissues are well-organized hierarchical structures that adapt to different stimuli to achieve a desired function. This study aims at explaining the complex chemical and biological mechanism that leads to the development of dental germs and teeth. It is impossible to pinpoint the exact moment when the process drifts or the aetiological causes of important diseases, such as the MIH, without a solid understanding of this long and fascinating process.